2010
DOI: 10.1111/j.1439-0434.2010.01759.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Pathological Characterization of Colletotrichum falcatum Infecting Subtropical Indian Sugarcane

Abstract: Red rot, caused by Colletotrichum falcatum, is the most significant problem of sugarcane worldwide. Pathological studies and three different marker systems were used to characterize 25 C. falcatum isolates collected from 18 subtropical sugarcane cultivars from 15 different sugarcane-growing regions of three north-eastern states of India to assess pathogen diversity. Of these 25 isolates, three were new (RR2A, RR15, RR83) from cultivars Co 7717, Co J83 and Co S88230, respectively, pathologically characterized o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…All the four clusters were representative of the three agroecological zones and the distribution of the isolates was not depending on the geographic area indicating a high genetic diversity at all locations. Kumar et al (2010) observed the same results; working with C. falcatum from sugarcane in India. Such variations could be due to similar climatic conditions, which might favor the coexistence of the isolates.…”
Section: Discussionsupporting
confidence: 54%
“…All the four clusters were representative of the three agroecological zones and the distribution of the isolates was not depending on the geographic area indicating a high genetic diversity at all locations. Kumar et al (2010) observed the same results; working with C. falcatum from sugarcane in India. Such variations could be due to similar climatic conditions, which might favor the coexistence of the isolates.…”
Section: Discussionsupporting
confidence: 54%
“…Genetic variabilities in C. falcatum isolates have been reported earlier using RAPD (Madan et al 2000;Mohanraj et al 2002;Suman et al 2005), analysis of ITS sequences (Malathi et al 2010), Universal Rice Primers (URP) and Inter Simple Sequence Repeat markers (Kumar et al 2011). The analysis of genomic DNA using PCR-based methods has proven to be a fast, sensitive and reliable method for determining genetic relationships among strains of the same phytopathogenic organisms (Ma and Michailides 2007).…”
Section: Resultsmentioning
confidence: 90%
“…The key morphological identification features of C. falcatum fungus are: its mycelium which is both intracellular and intercellular, asexual fruiting bodies known as acervuli (minute, velvety and formed on the surface of the host part), often with setae (dark-pigmented, unbranched, thick-walled sterile hyphae usually pointed at the tip), having hyaline, linear or club shaped conidiophores producing elongated, single celled, thin walled, uninucleate, colourless, sickle shaped (Falcate), slimy conidia having granular protoplasm with a large oil globule, thick walled, greenish black chlamydospores and the presence of appressoria (thick-walled swellings at the end of a hypha or germ tube useful for attaching the fungus to the host surface before penetration of the tissue), presence or absence of the telomorph, colony colour and growth, production of pigments and growth rate which are mostly used for genetic characterization [9,10,44,45].…”
Section: Species: Falcatummentioning
confidence: 99%
“…The characterization of pathogen has primarily been based upon variation in colour, conidial size and shape, appressoria, colony characters, host association and sporulation [60][61][62][63][64]. But this phenotypic identification is time consuming, expertise specific and not always fully discriminative [45].…”
Section: Diagnostic Measuresmentioning
confidence: 99%
See 1 more Smart Citation